Annual Plan 1993-94 Volume-III General Areas Government of Assam - Planning Commission (Planning Commission, 1993)
During 1992-93 an amount of Rs. 18.00 crores was allocated for this project with the works programme of completing remaining works of permanent residential buildings, finishing works of power house building and part of the concreting of the Dam etc. But due to drastic cut in the plan size of 1992-93 an amount of Rs. 5.00 crores could only be provided. This has adversely affected the works programme envisaged earlier. Expenditure incurred in 1992-93 upto 31-12-92 is Rs. 2.798 crores. An amount of Rs. 20.00 crores has been prepared during the year 1993-94.
Government of Assam, Planning and Development Department
Government of Assam, Planning and Development Department